An Empirical Study of the Trends in Real Estate Prices in Chandigarh (India) - Mittal, Bharat (2007)
Indian real estate has huge potential demand in almost every sector especially commercial, residential, retail, industrial, hospitality, healthcare, etc. Commercial office space requirement is led by the burgeoning outsourcing and Information Technology Industry. The leaders of the IT/ITES world have set up or are setting up their centres in India. Estimated demand from IT/ITES sector alone is expected to be 150mn sq. ft. of space across the major cities by 2010. In residential sector there is housing shortage of 22.4 million units out of which 6.7 million are in urban India. The increase in purchasing power and exposure to organized retail formats has redefined the consumption pattern. As a result the country has experienced mushrooming of retail projects across the cities. The main growth thrust is coming due to favourable demographics, increasing purchasing power, existence of customer friendly banks & housing finance companies, professionalism in real estate and favourable reforms initiated by the government to attract global investors. All these factors have resulted in increased attention of global investors towards Indian real estate than ever before. By using data collected from property dealers and consultants in Chandigarh, we will study trends in prices of land in Chandigarh, its suburbs (Zirakpur) and rural areas. We will also study how the housing market has behaved in Chandigarh over the past 10 years.